The Jewish Bishop and the Chinese Bible : Place of publication not identifiedJ. Schereschewsky (1831-1906) - Eber, Irene, 1929- (Studies in Christian Mission, 1999)
A study of the life and times of Bishop Place of publication not identifiedJ. Schereschewsky (1831-1906) and his translation of the Hebrew Old Testament into northern vernacular (Mandarin) Chinese. Based largely on archival materials, missionary records and letters, the book includes an analysis of the translated Chinese text together with Schereschewsky's explanatory notes. The book examines his Jewish youth in Eastern Europe, conversion, American seminary study, journey to Shanghai and Beijing, mission routine, the translating committee's work, his tasks as Episcopal bishop in Shanghai and the founding of St. John's University. Concluding chapters analyze the controversial "Term Question" (the Chinese term for God) and Schereschewsky's techniques of translating the Hebrew text. Included are useful discussions of the Old Testament's Chinese reception and the role of this translation for subsequent Bible translating efforts.